Targeting proteins for proteasomal degradation—a new function of Arabidopsis ABI1 protein phosphatase 2C - Ludwików, Agnieszka (Frontiers in Plant Science, 2015)
The ubiquitin/26S proteasome system (UPS) has been implicated in the regulation of many physiological processes including hormone signaling. The plant hormone abscisic acid (ABA) employs the UPS to control its own synthesis and signaling and to regulate stress response and tolerance. Among the known effectors of ABA signalling, the ABI1 (abscisic acid-insensitive 1) protein phosphatase, which belongs to group A of the type 2C protein phosphatases, is recognised as a key component of the pathway. Molecular and genetic evidence implicates this protein phosphatase in numerous plant responses. This mini-review discusses recent progress in understanding the role of ABI1 in ABA signaling, with particular emphasis on recent data that link ABI1 to protein degradation via the UPS.